Crosslinked chitosan–montmorillonite composite and its magnetized counterpart for the removal of basic fuchsin from wastewater: Parametric optimization using Box-Behnken design - Ahmed S., El-Shafie (2024)
Treating wastewater polluted with organic dyestuffs is still a challenge. In that vein, facile synthesis of a structurally simple composite of chitosan with montmorillonite (CS-MMT) using glutaraldehyde as a crosslinker and the magnetized analogue (MAG@CS-MMT) was proposed as versatile adsorbents for the cationic dye, basic Fuchsin (FUS). Statistical modeling of the adsorption process was mediated using Box-Behnken (BB) design and by varying the composite dose, pH, [FUS], and contact time. Characterization of both composites showed an enhancement of surface features upon magnetization, substantiating a better FUS removal of the MAG@CS-MMT (%R = 98.43 %) compared to CS-MMT (%R = 68.02 %). The surface area analysis demonstrates that MAG@CS-MMT possesses a higher surface area, measuring 41.54 m2/g, and the surface analysis of the magnetized nanocomposite, conducted using FT-IR and Raman spectroscopies, proved the presence of FeO peaks. In the same context, adsorption of FUS onto MAG@CS-MMT fitted-well to the Langmuir isotherm model and the maximum adsorption capacities (qm) were 53.11 mg/g for CS-MMT and 88.34 mg/g for MAG@CS-MMT. Kinetics investigation shows that experimental data fitted well to the pseudo-second order (PSO) model. Regeneration study reveals that MAG@CS-MMT can be recovered effectively for repeated use with a high adsorption efficiency for FUS.